PENGARUH SUKU BUNGA, KURS RUPIAH, DAN HARGA EMAS TERHADAP RETURN SAHAM PERUSAHAAN LQ 45 YANG TERDAFTAR DI BURSA EFEK INDONESIA - Harsuti, Harsuti; Wahyuningsih, Endang Sri; Suzana, Andhi Johan; Lestari, Herwiek Diyah; Koesoemasari, Dian S.P; Kartika, Rosalia Anindia Sari (POLITEKNIK LP3I JAKARTA, 2024)
This research aims to analyze the significance of the influence of interest rates, rupiah exchange rates and gold prices on stock returns in LQ 45 companies listed on the Indonesia Stock Exchange. The population in this study was 60 LQ 45 companies listed on the Indonesia Stock Exchange from 2016 to 2020, while the sample in this study used a purposive sampling technique to obtain 30 companies. The analysis technique used is panel data regression analysis technique with the Eviews 9 program. The research results show that the rupiah exchange rate has a significant negative effect on stock returns while the gold price has a significant negative effect on stock returns. Meanwhile, interest rates do not have a significant effect on stock returns. The implication of this research is that investors must know and be able to predict the state of interest rates, the rupiah exchange rate and the price of gold before investing in shares. Suggestions for further research are to add other macro variables (inflation, world oil prices and other commodity prices) and internal company variables in the hope of being able to analyze more representative stock return movements. Keywords: Stock Return, Interest Rate, Rupiah Exchange, Gold Price